"Codeine Is My Helper": Misuse of and Dependence on Codeine-Containing Medicines in South Africa. (February 2017) - Van Hout, Marie Claire; Rich, Eileen; Dada, Siphokazi; Bergin, Michael
Misuse of codeine-containing medicines is an emerging global public health concern. The majority of research has been conducted in developed countries (European Members States, Australia, the United States). This study aimed to gain an understanding of unique individual and collective experiences of trajectories of codeine misuse and dependence in South Africa. In-depth interviews were conducted with a purposive sample of adult codeine misusers and dependents ( n = 25). Narratives were analyzed using the empirical phenomenological psychological five-step method. Nine themes with 63 categories emerged, with two additional high levels of abstraction. Findings are illustrated: participant profile and product preferences, motives for use, transitioning to misuse and dependence, pharmacy purchasing and alternative sourcing routes, effects and withdrawal experiences, help-seeking and treatment experiences, and strategies for prevention. The study underscores the need for continued support for enhanced patient awareness of risk of habit forming use and related health consequences and professional pharmacovigilance.